Assessment of salivary immunoglobulin A, interleu-kin-6 and C-reactive protein in chronic kidney dis-ease patients on hemodialysis and on conservative treatment - Salim , Ithar K; Diajil , Ameena R (Journal of Baghdad College of Dentistry, 2022)
Background: Chronic kidney disease is a gradual loss of kidney function with diabetes and hypertension as the leading cause. Chronic kidney disease is one of these systemic diseases that can affect salivary contents. Aims: This study aimed to assess salivary immunoglobulin A, interleukin-6 and C- reactive protein in chronic kidney disease patients on hemodialysis and those on conservative treatment in comparison with control subjects. Materials and methods: Ninety subjects were included in this study divided into three groups: 30 patients with chronic kidney disease on hemodialysis for at least 6 months ago; 30 patients with chronic kidney disease on conservative treatment and 30 healthy control subjects. Secretory immunoglobulin A, interleukin-6 and C- reactive protein in saliva samples were measured by enzyme-linked immunosorbent assay ELISA. Results: No significant difference in salivary immunoglobulin A level among study groups was seen. A significant increase in salivary interleukin-6 and C- reactive protein in both chronic kidney disease patients on hemodialysis and those on conservative treatment compared to the control group. While, no significant salivary IL-6 and CRP differences were seen between both patient groups, on hemodialysis and conservative treatment. Conclusions: There was no significant difference among chronic kidney disease patients on hemodialysis, on conservative treatment and control healthy subjects regarding to salivary IgA while Salivary interleukin -6 and C- reactive protein was significantly higher in chronic kidney disease patients on hemodialysis and those on conservative treatment compared to healthy subjects.